Fractionated stereotactic radiotherapy of brainstem metastases: clinical outcome and prognostic factors - Krämer, Anna Sabrina; Hahnemann, Laura; Schunn, Fabian; Grott, Christoph A.; Thomas, Michael; Christopoulos, Petros; Lischalk, Jonathan W; Hörner-Rieber, Juliane; Hoegen-Saßmannshausen, Philipp; Eichkorn, Tanja; Deng, Maximilian; Meixner, Eva; et al. (Clinical and translational radiation oncology, 2025)
Introduction - Brain metastases (BM) are the most common malignancy in the central nervous system (CNS) and observed in approximately 30% of cancer patients. Brainstem metastases (BSM) are challenging because of their location and the associated neurological risks. There are still no general therapeutic recommendations in this setting. Stereotactic radiosurgery (SRS) is one of few possible local therapy options but limited due to the tolerance dose of the brainstem. There is still no standard regarding the optimal dose und fractionation. - Methods - We retrospectively analyzed 65 patients with fractionated stereotactic radiotherapy (fSRT) for 69 BSM. FSRT was delivered at a dose of 30 Gy in six fractions prescribed to the 70 % isodose performed with Cyberknife. Overall survival (OS), local control (LC) and total intracranial brain control (TIBC) were analyzed via Kaplan-Meier method. Cox proportional hazards models were used to identify prognostic factors. - Results - Median follow-up was 27.3 months. One-year TIBC was 35.0 % and one-year LC was 84.1 %. Median OS was 8.9 months. In total, local progression occurred in 7.7 % and in 8.2 % symptomatic radiation-induced contrast enhancements (RICE) were diagnosed. In univariate analysis the Karnofsky performance scale index (KPI) (p = 0,001) was an independent prognostic factor for longer OS. Acute CTCAE grade 3 toxicities occurred in 18.4 %. - Conclusion - FSRT for BSM is as an effective and safe treatment approach with high LC rates and reasonable neurological toxicity despite the poor prognosis in this patient cohort is still very poor. Clinical and imaging follow-up is necessary to identify cerebral progression and adverse toxicity including RICE.
Online verfügbar 21 November 2024, Version des Artikels 23 November 2024
Gesehen am 04.07.2025